(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2000)
One of the daring theses that question traditional periodization schemes was the one advanced by the Cambridge History of Latin American Literature through the article on "Lyric Poetry of Eighteenth and Nineteenth Centuries" written by Andrew Bush. This forceful thesis deserves all our attention also in the field of the novel and literature, in general, given that at the very moment in which we try to formulate a clear definition of the terms involved that would allow us a clear periodization, both in the content as well as temporal limits, we encounter a series of serious problems.